TINDAK TUTUR DAN PERWATAKAN DALAM CERPEN HARGA SEORANG PEREMPUAN KARYA OKA RUSMINI - Wijana, I Dewa Putu (Sintesis, 2008)
Eventhough it has been aware that the speech uttured by the novel characters can be used to identify their own attitudes and personalities, the pragmatic studies on the use of utturance types in relation to the literary characterization are rare. This study seeks to prove that speech acts together with their strategies in literary works are essentially the reflection of those story characters behaviour, and therefore pragmatic approach is an important tool for analyzing and understanding characters of literary works.KEY WORDS character, speech act, utturance